METHODS OF IMPROVING PHONETIC SKILLS IN TEACHING A FOREIGN LANGUAGE AT SCHOOL - Jumanazarov Umid Umirzakovich, Almatova Umida Islomovna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The following article deals with the problem of modern didactic parameters of the formation of students' phonetic skills in foreign language classes. The development of modern didactic parameters serves to ensure the effectiveness of the development of pupils' phonetic skills in foreign language classes. The development of modern didactic parameters clarifies the purpose of a number of education. In particular, special attention should be paid into the development of pupils' interests, abilities, thinking, attention, perception, memory, emotions, will, cognition and practical skills; because as the pupil's thinking develops, he or she feels the need to acquire new knowledge.